A novel vapor injection structure on the blade of a rotary compressor. (5th May 2016) - Liu, Xingru; Wang, Baolong; Shi, Wenxing; Zhang, Penglei
Highlights: A novel vapor injection structure on blade for rotary compressor is proposed. The η v and system mass flowrate are enhanced 1.8–2.7% and 26.6–57.2%, respectively. The heating capacity and COP are improved 23.1–48.9% and 3.2–8.0%, respectively. Abstract: Heat pumps with rotary compressors operating in low ambient temperature will face heavy performance degradation. A novel vapor injection structure on the blade for the rotary compressor has been proposed in this paper to overcome the back-flowing drawback of the traditional cylinder injection structure and increase the injection area. Based on a verified numerical model, the performance of a rotary compressor with the blade injection structure has been investigated. The results indicate that: the proposed vapor injection structure can eliminate the back-flowing of the injected refrigerant; compared to the traditional injection structure, the new structure can enhance the volumetric efficiency and mass flow-rate by 1.8–2.7% and 26.6–57.2%, respectively; and compared to the traditional injection structure, the new structure can increase the heating capacity and COP by 23.1–48.9% and 3.2–8.0%, respectively.